PENGARUH STRATEGI TRUE OR FALSE TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN PPKN DI SEKOLAH DASAR - Mufliha, Nuraini; Slam, Zaenul (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study aims to determine the effect of true or false strategies on students' critical thinking skills in civics subjects at SDN Kapuk 16 morning. The research method used is a quasi-experimental method and the research design used is the Non Equivalent Control Group Design. Sampling was carried out using a purposive sampling technique for research samples in class III A (Experimental Class) totaling 28 students and class III B (Control Class) totaling 28 students. The research instrument used was in the form of multiple choice students' critical thinking skills totaling 20 questions. The data analysis technique used in this study was the normality test using the Shapiro Wilk technique. Homogeneity test using One Way Anova. Then proceed with the posttest hypothesis test using Mann Whitney U at a significance level of 5% (0.05) obtained sig. (2-tailed) of 0.000 with the conclusion H0 being rejected (there is a true or false strategy effect on students' critical thinking skills). The critical thinking of students in the experimental group increased higher (N-gain 0.66 medium category) than students in the control group (N-gain 0.21 low category).